P53 knockout mice are protected from cocaine-induced kindling behaviors via inhibiting mitochondrial oxidative burdens, mitochondrial dysfunction, and proapoptotic changes. (March 2019) - Mai, Huynh Nhu; Sharma, Naveen; Jeong, Ji Hoon; Shin, Eun-Joo; Pham, Duc Toan; Trinh, Quynh Dieu; Lee, Yu Jeung; Jang, Choon-Gon; Nah, Seung-Yeol; Bing, Guoying; Kim, Hyoung-Chun
Abstract: Previously we demonstrated that p53 mediates dopaminergic neurotoxicity via inducing mitochondrial burdens and proapoptotsis. However, little is known about the role of p53 in the excitotoxicity induced by psychostimulant, such as cocaine. Cocaine-induced kindling (convulsive) behaviors significantly increased p53 expression in the brain. Cocaine-induced p53 expression was more pronounced in hippocampus than in striatum or prefrontal cortex. Genetic depletion of p53 significantly attenuated cocaine-induced convulsive behaviors, followed by c-Fos immunoreactivity, and oxidative burdens in the hippocampus of mice. The antioxidant potentials mediated by genetic depletion of p53 were more pronounced in the mitochondrial-than cytosolic-fraction. Depletion of p53 significantly attenuated the changes in mitochondrial transmembrane potential, intramitochondrial Ca 2+ level, and mitochondrial oxidative burdens induced by cocaine. Consistently, depletion of p53 significantly inhibited mitochondrial p53 translocation, and cleaved-PKCδ induced by cocaine. In addition, depletion of p53 protected from cytosolic cytochrome c release, and pro-apoptotic changes induced by cocaine. Importantly, the protective/anticonvulsant potentials by genetic depletion of p53 were comparable to those by pifithrin-μ (PFT), a p53 inhibitor. Our results suggest that depletion of p53 offers anticonvulsive and neuroprotective potentials mainly via attenuating mitochondrial oxidative burdens, mitochondrial dysfunction, and pro-apoptotic signalings against cocaine-induced convulsive neurotoxicity. Graphical abstract: Image 1 Highlights: P53 inhibition protects against cocaine-induced kindling (convulsive) behaviors. Cocaine-induced p53 expression is most pronounced in hippocampus. Cocaine-induced oxidative stress is more evident in mitochondria than in cytosol. P53 depletion attenuates cocaine-induced mitochondrial dysfunction. P53 depletion attenuates cocaine-induced pro-apoptotic phenomena.